Do CAADP processes make a difference to country commitments to develop agriculture? The case of Ghana - Kolavalli, Shashidhara; Flaherty, Kathleen; Al-Hassan, Ramatu M.; Baah, Kwaku Owusu (International Food Policy Research Institute, 2010)
The objective of this paper is primarily to understand how continental initiatives such as CAADP can and do influence country commitment to seek agriculture-led development. This paper employs Ghana as a case study to examine whether CAADP processes leading up to and including the country roundtable process enhance the visibility of the role of agriculture as a means of reducing poverty. The study explores whether countries take the leadership in adopting the CAADP framework. First, the paper provides perspective on the agricultural sector in Ghana and the role of agriculture in development strategies. Further, it reviews how the processes for implementation of CAADP have evolved and how they have influenced implementation in Ghana. It evaluates what impact CAADP may have on the content of agricultural policies in Ghana. Finally, the paper makes some suggestions for improving CAADP implementation.